2022
DOI: 10.3390/biology11101513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intermittent Hypoxic Training on Selected Biochemical Indicators, Blood Rheological Properties, and Metabolic Activity of Erythrocytes in Rowers

Abstract: The study assessed the effect of 3-week intermittent hypoxic training on blood biochemical indicators (blood morphology, fibrinogen), blood rheological properties (erythrocyte deformability, aggregation), erythrocyte enzymatic activity (acetylcholinesterase), and maximal oxygen uptake in competitive rowers. Fourteen male rowers were divided into two equal groups: experimental, training on ergometers under normobaric hypoxia (FiO2 = 16.0%), and control, training on ergometers under normoxia (FiO2 = 21%). Fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This could be explained by the methodological assumptions of this study - blood samples were taken immediately after the last training. Other authors most often analysed these variables a few days after completing the training plan ( Teległów et al, 2022 ), thus, there is more time for some adaptation changes. The current study was designed to assess response to submaximal interval training after IHT in male participants, rather than just resting data measured a few days after training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be explained by the methodological assumptions of this study - blood samples were taken immediately after the last training. Other authors most often analysed these variables a few days after completing the training plan ( Teległów et al, 2022 ), thus, there is more time for some adaptation changes. The current study was designed to assess response to submaximal interval training after IHT in male participants, rather than just resting data measured a few days after training.…”
Section: Discussionmentioning
confidence: 99%
“…Regular training lead to increase of mRNA expression for erythropoietin and for EPO receptor in bone marrow ( Suzuki, 2015 ). Despite this, there is no much data regarding the impact of prolonged hypoxia training on red blood cell hemorheology ( Lin et al, 2021 ; Park et al, 2022a ; Teległów et al, 2022 ). Exercise in hypoxia at different oxygen condition did not altered red blood cell aggregation in healthy male despite of significant increase blood lactate concentration ( Moon et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The obtained intergroup differences in the aggregation amplitude index may result from different levels of body hydration. This factor has been proven to impact blood rheology [ 40 , 41 ]. A valuable supplement to the research would probably be to determine the initial average water content in the body.…”
Section: Discussionmentioning
confidence: 99%
“…First, the effectiveness of IHT may arise from its specific underlying mechanism or methodological design (Czuba, Fidos-Czuba et al, 2018). Unlike HH and HL, numerous studies have indicated that the hypoxic exposure of IHT is inadequate to substantially alter hematological parameters (Czuba et al, 2014;Czuba et al, 2019;Ambroży et al, 2020;Kim et al, 2021;Park et al, 2022;Teległów et al, 2022), and the potential mechanism for enhancing aerobic capacity primarily involves specific molecular adaptations in peripheral tissues (Ponsot et al, 2006;Zoll et al, 2006;Neya et al, 2007). It is worth noting that Czuba et al posited that a hematological mechanism is more effective in enhancing aerobic capacity (Czuba et al, 2018), and the diverse adaptations due to IHT contributes greatly to exercise (Green et al, 2000;Hamlin et al, 2010;Park et al, 2016;Saunders et al, 2004), which can also serve as a valuable metric for evaluating aerobic performance (Levine and Stray-Gundersen, 2005).…”
Section: Discussionmentioning
confidence: 99%